Impact of Non-Oil Export on Non-Oil Economic Growth in Saudi Arabia - Aljebrin, Mohammed A. (International Journal of Economics and Financial Issues, 2017)
This study empirically estimates the critical parameters of non-oil export impact on non-oil economic growth in Saudi Arabia for the period 1988-2014 by using ordinary least squares (OLS) and error correction model approach. The empirical results obtained show that, in both short run and long run, there are positive and significant relationship between the non-oil economic growth and non-oil exports. There is also positive and significant relationship between non-oil economic growth and capital in both long run and short run. On the other hand, there is positive and significant relationship between non-oil economic growth and labor in the long run but positive and insignificant in the short run. The error correction is correctly negatively signed and highly significant and has a large magnitude (-0.537) suggesting a rapid adjustment process, which means that, if non-oil GDP is 1 percent out of equilibrium, a 53.7 percent adjustment towards equilibrium will take place within the first year. Keywords: Non-oil Export, open Economy, Non-Oil GDP, Saudi Arabia. JEL Classifications: F11, F14, F41, F43